ANALISIS COMMON SIZE UNTUK MENILAI KINERJA KEUANGAN SEBAGAI DASAR PENGAMBILAN KEPUTUSAN PADA PT.PELNI (PERSERO) CABANG PAREPARE - Mardiana, Mardiana (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to assess the financial performance of PT Pelni (Persero) Cabang Parepare by using general measurement analysis as a basis for decision making. The research approach chosen is descriptive quantitative because the oncoming is appropriate with the objectives of this study. The data research was collected through observation, documentation, and interviews. The data used are secondary in the form of income statements and balance sheets. The results of this study indicate that the company's net profit from year to year fluctuates due to non-captive activities, namely loading and unloading. Unloading is referring to as labor costs and business service fees. The more costs incurred in loading and unloading, the less revenue is received. While a notice of the general balance sheet analysis for 2016 and 2017, debt increased due to operational costs or business costs and fixed activities that the company wanted to finance.